2001
DOI: 10.1515/cclm.2001.088
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Carbohydrate Antigen 19-9 (CA 19-9) in Patients with Echinococcus Infection

Abstract: The carbohydrate antigen 19-9 (CA 19-9), a determinant (sialylated lacto-N-fucopentaose 119) of a circulating oligosaccharide antigen, is a frequently used tumor marker. Echinococcus spp. infects humans throughout the world and may be able to synthesize closely related molecules which could interfere with the measurement and interpretation of CA 19-9 concentration. The main objective of the present study was to determine the range of CA 19-9 levels in the sera of patients infected by E. granulosus (cystic hyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…22). A basic link among cancer and the tumor-like growth and behavior of the E. multilocularis metacestode was given by the identification and characterization of the 14-3-3 protein overexpressed at the metacestode stage of the parasite and by the frequent expression of elevated carbohydrate antigen CA 19Ϫ9 levels (sialylated lacto-N-fucopentaose 119) in many E. multilocularis infected patients (24,25). Nevertheless, the presence of an ␣-linkage in structure B cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…22). A basic link among cancer and the tumor-like growth and behavior of the E. multilocularis metacestode was given by the identification and characterization of the 14-3-3 protein overexpressed at the metacestode stage of the parasite and by the frequent expression of elevated carbohydrate antigen CA 19Ϫ9 levels (sialylated lacto-N-fucopentaose 119) in many E. multilocularis infected patients (24,25). Nevertheless, the presence of an ␣-linkage in structure B cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The epitope recognized by anti CA 19-9 antibodies is the sialylated Lewis-a antigen. This antigen ends with a characteristic carbohydrate sequence, and very similar sialylated fucose-containing glycans have been found in hydatid membranes of E. granulosus (2). These substances may bear the Lewis-a antigen or closely related structures, which are recognized by anti CA 19-9 antibodies, producing an elevation of CA 19-9 (11).…”
Section: Discussionmentioning
confidence: 89%
“…Pfister et al (2) showed that 11% of the patients with liver hydatidosis caused by E. granulosus presented an abnormal value of CA 19-9. On the other hand, Yuksel et al (1) noticed in their series of 40 patients that 65% presented a value above cut-off.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations